Identifikasi Tipe Kepribadian Seseorang Ditinjau Dari Teori Carl Jung - Ni Made Sulastri (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Personality is a collection of attitudes, behavior, emotional and individual reactions that are influenced by a person's environment and life experiences. In measuring personality, various methods can be used, such as scientific, semi-scientific and pre-scientific methods. In this research, the method for measuring a person's personality is to use scientific methods through an identification process to recognize oneself and others as well as personality identification based on personality theories from experts. Personality theories from various experts can be the basis for determining a person's personality type. The results of the research show that personality types according to Carl Jung divide human personality into two groups, namely introverts and extroverts, someone who has an introverted personality tends to have independence. In this phase, according to Carl Jung, individuals build more independent relationships without relying on other people. In the research It can be concluded that someone who has an introverted personality can also develop strong and meaningful social relationships with other people.